2011
DOI: 10.1086/658921
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Context of Endophyte Symbioses: Interacting Effects of Water Stress and Insect Herbivory

Abstract: Symbiotic associations between grasses and fungal endophytes are generally regarded as mutualistic, yet benefits to host plants may vary with environmental context. Previous studies have emphasized how endophytes influence plant responses to single stressors. In contrast, the outcome of endophyte-grass interactions under simultaneous biotic and abiotic stresses remains poorly explored. We hypothesized that benefits from endophyte symbiosis become most apparent in ''complex'' environments where hosts experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The relevance of drought as regulator for plant-microbe interactions has been demonstrated for fungal endophytes (Miranda et al 2011;Vesterlund et al 2011;Yule et al 2011). For instance, Yule et al (2011) found that a moderate water-stress treatment strengthened the positive effect of endophytes on plant biomass and aphid incidence, which was lost under a highwatering regime.…”
Section: Amino Acids Determinationmentioning
confidence: 99%
“…The relevance of drought as regulator for plant-microbe interactions has been demonstrated for fungal endophytes (Miranda et al 2011;Vesterlund et al 2011;Yule et al 2011). For instance, Yule et al (2011) found that a moderate water-stress treatment strengthened the positive effect of endophytes on plant biomass and aphid incidence, which was lost under a highwatering regime.…”
Section: Amino Acids Determinationmentioning
confidence: 99%
“…A similar mechanism may be behind the results of Vásquez- de-Aldana et al (2011), who showed that root exudates of red fescue (Festuca rubra) had a greater inhibitory effect on the germination and seedling growth of four target species when infected with a fungal endophyte, Epichloë festucae. Endophyte infection can be beneficial to the host plant with respect to many factors including increased resistance to drought, salt stress, nematodes, mammalian and insect herbivores, and bacterial and fungal pathogens (Kimmons et al, 1990;Li et al, 2009;Ownley et al, 2010;Sabzalian and Mirlohi, 2010;Miranda et al, 2011;Rocha et al, 2011). Rudgers and Orr (2009), however, were able to show that soils conditioned by non-native tall fescue (Lolium arundinaceum) that was infected by the fungal endophyte, Neotyphodium coenophialum, were able to reduce the biomass of Elaeagnus umbellata, Fraxinus pennsylvanica, and Platanus occidentalis.…”
Section: Increases In Allelochemical Toxicity Through Microbialmentioning
confidence: 99%
“…We analysed those traits usually affecting preference by domestic herbivores (Bailey et al 1996;Jung et al 1997) that, in turn, can be also modified by the endophyte (Miranda et al 2011;Soto-Barajas et al 2016). We analysed those traits usually affecting preference by domestic herbivores (Bailey et al 1996;Jung et al 1997) that, in turn, can be also modified by the endophyte (Miranda et al 2011;Soto-Barajas et al 2016).…”
Section: Plant and Animal Measurementsmentioning
confidence: 99%